2023
DOI: 10.1038/s41579-023-00878-2
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of SARS-CoV-2

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused millions of deaths and substantial morbidity worldwide. Intense scientific effort to understand the biology of SARS-CoV-2 has resulted in daunting numbers of genomic sequences. We witnessed evolutionary events that could mostly be inferred indirectly before, such as the emergence of variants with distinct phenotypes, for example transmissibility, severity and immune evasion. This Review explores the mechanisms that generate genetic variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
277
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 461 publications
(380 citation statements)
references
References 219 publications
7
277
2
1
Order By: Relevance
“…SARS-CoV-2 continues to cause disproportionate morbidity and mortality in older adults (1). Although vaccines effectively reduce this burden, immunity wanes in the months following vaccination (2,3) and the virus continues to evolve to escape population immunity (4,5). As newer versions of vaccines are adapted to recent SARS-CoV-2 variants (i.e., bivalent vaccine) (6), we must continue to determine how effective these vaccines are over time and against emerging variants and especially in vulnerable populations.…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 continues to cause disproportionate morbidity and mortality in older adults (1). Although vaccines effectively reduce this burden, immunity wanes in the months following vaccination (2,3) and the virus continues to evolve to escape population immunity (4,5). As newer versions of vaccines are adapted to recent SARS-CoV-2 variants (i.e., bivalent vaccine) (6), we must continue to determine how effective these vaccines are over time and against emerging variants and especially in vulnerable populations.…”
Section: Introductionmentioning
confidence: 99%
“…VOCs poses a challenge to the protection conferred by the COVID‐19 vaccines that received early approval for use, as VOCs contain mutations that may cause immune escape (Figure 4). 38 Subsequently, mRNA vaccines were shown to elicit robust antibody responses against many SARS‐CoV‐2 VOCs in children and adolescents. A study that assessed the VOC‐specific humoral responses including binding titers of several immunoglobulin isotypes and FcγR‐binding after two doses of BNT162b2 found children and adolescents maintained binding IgA and IgG against all four pre‐Omicron VOCs tested (Alpha, Beta, Gamma, and Delta) 62 .…”
Section: Cross‐variant Reactivitymentioning
confidence: 99%
“…Immune responses against variants of concern (VOCs), some of which can be prone to vaccine escape, are described (Figure 4). 38 As almost all children have or soon will be infected with SARS‐CoV‐2, we present evidence available for hybrid immunity, which is the synergistic immune response between infection and vaccination 39 . The information from this review aims to be useful for public health policymaking, promoting safe school environment, and ensuring children's best future outcomes for living with COVID‐19 long term, 40,41 now that the WHO has declared COVID‐19 no longer a public health emergency of international concern 42…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of quasispecies data already provided valuable information for managing molecular contact tracing for other RNA viruses as human immunodeficiency virus (HIV) and human hepatitis C virus (HCV) 14 which, unlike coronaviruses, lack a 3′ exonuclease proofreading mechanism in their replication machinery 15 . However, it is well documented how different mechanisms may introduce mutations into the SARS‐CoV‐2 genome 16 . In addition to RNA replication errors, the generation of genetic diversity may be the result of multiple, viral and host‐mediated events involving genome size, replication mechanisms, postreplicative repair, spontaneous amino acid variation, environmental changes, and host‐mediated genome editing 17 .…”
Section: Introductionmentioning
confidence: 99%
“…15 However, it is well documented how different mechanisms may introduce mutations into the SARS-CoV-2 genome. 16 In addition to RNA replication errors, the generation of genetic diversity may be the result of multiple, viral and hostmediated events involving genome size, replication mechanisms, postreplicative repair, spontaneous amino acid variation, environmental changes, and host-mediated genome editing. 17 Several studies have shown that intrahost genomic variation is a common trait of SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%